PENGARUH TERAPI MUSIK ROHANI DENGAN STATUS HEMODINAMIK PADA PASIEN DI RUANG ICU (Nursing Care Journal, 2024)
The Intensive Care Unit, ICU, is a hospital unit with staff and equipment to manage patients with life-threatening diseases, trauma, and complication due to organ or system dysfunction. The care is important because the patients may survive with intensive care and medication. Hemodynamic changes influenced the patient's conditions in ICU so specific monitoring and therapeutic actions are important. One of the therapies to apply is spiritual music therapy to improve the life quality of patients through the nervous system of the patients. This mechanism improves the psychological level, sleeping quality, and convenience of the patients due to the decreased beat rhythm. This research determined the influence of spiritual music therapy on the hemodynamic status of the patients. This pre-experimental research applied one group pretest-posttest without a control group. The sample consisted of 34 respondents taken with purposive sampling. The applied statistic test was paired t-test if the results were normal, starting from the blood pressure and the pulse. If the results were not normal, the researcher would apply the Wilcoxon test for saturation and respiratory rate. The results showed the p-value of systolic, diastolic, and oxygen saturation was 0.004 lower than 0.05; pulse with 0.005 lower than 0.05; and respiration with 0.263, higher than 0.05. The results showed the influence of spiritual music therapy on systolic, diastolic, oxygen saturation, and pulse. On the other hand, respiration did not influence the patients after providing spiritual music therapy.